2019
DOI: 10.3390/v11050453
|View full text |Cite
|
Sign up to set email alerts
|

Global Transcriptomic Analysis Reveals Insights into the Response of ‘Etrog’ Citron (Citrus medica L.) to Citrus Exocortis Viroid Infection

Abstract: Citrus exocortis viroid (CEVd) is the causal agent of citrus exocortis disease. We employed CEVd-infected ‘Etrog’ citron as a system to study the feedback regulation mechanism using transcriptome analysis in this study. Three months after CEVd infection, the transcriptome of fresh leaves was analyzed, and 1530 differentially expressed genes were detected. The replication of CEVd in citron induced upregulation of genes encoding key proteins that were involved in the RNA silencing pathway such as Dicer-like 2, R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(46 citation statements)
references
References 82 publications
2
42
0
Order By: Relevance
“…Implementation of high-throughput methods, including microarray and RNA-seq technology, enable wide transcriptome profiling, which is very helpful in understanding the molecular basis of plant/host-pathogen interactions. Taking advantage of these technologies, there are many studies about leaf transcriptome analysis during viroid infection in various host plants, including PSTVd [10,11,12,13,14], citrus exocortis viroid (CEVd) [15,16,17], citrus viroid III (CVd-III) [18], peach latent mosaic viroid (PLMVd) [19], hop stunt viroid (HSVd) [20,21], chrysanthemum stunt viroid CSVd) [22], hop latent viroid (HLVd) [23,24], and citrus bark cracking viroid (CBCVd) [23,24,25]. Moreover, there is also data about gene expression alterations in PSTVd-infected tubers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of high-throughput methods, including microarray and RNA-seq technology, enable wide transcriptome profiling, which is very helpful in understanding the molecular basis of plant/host-pathogen interactions. Taking advantage of these technologies, there are many studies about leaf transcriptome analysis during viroid infection in various host plants, including PSTVd [10,11,12,13,14], citrus exocortis viroid (CEVd) [15,16,17], citrus viroid III (CVd-III) [18], peach latent mosaic viroid (PLMVd) [19], hop stunt viroid (HSVd) [20,21], chrysanthemum stunt viroid CSVd) [22], hop latent viroid (HLVd) [23,24], and citrus bark cracking viroid (CBCVd) [23,24,25]. Moreover, there is also data about gene expression alterations in PSTVd-infected tubers [26].…”
Section: Introductionmentioning
confidence: 99%
“…Citrus exocortis viroid (CEVd), which belongs to the Pospiviroidae family, consists of around 370 nucleotides and has a broad range of hosts including tomato plants (Solanum lycopersicum L.). CEVd symptoms in tomato include stunting, epinasty, midvein necrosis, chlorosis and leaf rugosity [4][5][6]. Some of these symptoms have been associated with those produced by ethylene, since plants exogenously treated with the ethylene-releasing compound ethephon, as well as mutants that over produce ethylene, display similar symptoms to those caused by CEVd [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in host transcriptome caused by viroid infection have been analyzed in various viroid–host combinations [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ]. Infected plants are characterized by the fluctuations in several observables such as expressions of genes involved in plant innate immunity, defense responses, signal transduction and hormone metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was shown in various viroid–host combinations that genes involved in plant innate immunity, mainly calcium-dependent protein kinase and mitogen-activated protein kinase cascade or genes involved in hypersensitive response, cell wall enhancement, and hormone signaling were activated by viroid infection. These observations also suggested that the expression of a large number of genes, such as those involved in defense responses, hormone metabolisms, signal transduction, photosynthesis, chloroplast, cell wall, and regulation of RNA expression are affected by viroid infection, leading to the development of disease symptoms [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%